Complete mitochondrial genome of the juvenile Gymnodiptychus dybowskii (Cypriniformes, Cyprinidae, Schizothoracinae) from Ili River by high-throughput sequencing and the phylogenetic relationship of Schizothoracinae species. Issue 1 (2nd January 2020) - Niu, Jiangong; Zhang, Tao; Liu, Hong; Hu, Jiangwei; Zhang, Renming; Zhang, Hui
Abstract: The complete mitochondrial genome of the juvenile Gymnodiptychus dybowskii collected from Ili River was determined by high-throughput sequencing. The mitogenome is a circular molecule 16, 657bp in length, including 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and a control region. The TAS, central CSB and CSB were detected in the control region. The gene contents of the mitogenome are identical to those observed in most bony fishes. The NJ phylogenetic tree showed that G. dybowskii clustered into one branch with the species from the same genus.